2020
DOI: 10.1021/acs.jpcc.0c04931
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Single-Atom Platinum–Oxygen Vacancy Defects for the Boosted Photosplitting Water H2 Evolution and CO2 Photoreduction: Experimental and Theoretical Study

Abstract: The incorporation of oxygen vacancy defects into the catalysts has been attracting significant interest for regulating the performance of photocatalysts. Single-atomic-site metal catalysts have also been paid ever-growing attention because they maximized the atom efficiency and thus generated excellent catalytic performance. Herein, we report the interaction of oxygen vacancy defects and decorated atomically dispersed metal Pt to boost the efficient photocatalytic process. Compared with TiO2 without oxygen def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(46 citation statements)
references
References 81 publications
1
43
0
Order By: Relevance
“…To confirm the key bond characteristics of adsorbed CO 2 anion, the vibration frequency calculations were obtained. Three key vibrational modes of CO 2 including symmetric (ν1), bending (ν2), and asymmetric (ν3) stretching modes were agreed to for other calculations for CO 2 anion adsorption on M 4 - TiO 2 surfaces [ 47 , 59 , 69 ].…”
Section: Resultssupporting
confidence: 76%
“…To confirm the key bond characteristics of adsorbed CO 2 anion, the vibration frequency calculations were obtained. Three key vibrational modes of CO 2 including symmetric (ν1), bending (ν2), and asymmetric (ν3) stretching modes were agreed to for other calculations for CO 2 anion adsorption on M 4 - TiO 2 surfaces [ 47 , 59 , 69 ].…”
Section: Resultssupporting
confidence: 76%
“…This is in accord with previous results that incorporation of P(V) and oxygen vacancies considerably inhibited the recombination rate of photogenerated e − -h + pairs. 45,47 The results above showed that P(V) doping at a moderate level stabilized Ti(III) and oxygen vacancies at a high concentration, leading to an enhanced light harvesting, charge separation, and transfer (Figure 6 and Figure 7).…”
Section: Chemical Composition and State Analysismentioning
confidence: 90%
“…1,44 The secondary emission peak was present at 450-550 nm and should be due to transition at subband induced by dopants and oxygen vacancies. 45 The spinach-leafarchitectured TiO 2 showed a redshift of more than 50 nm in the secondary emission peak in comparison with P25. The redshift confirms that extra band levels were introduced by P(V) and Ti(III) dopants.…”
Section: Chemical Composition and State Analysismentioning
confidence: 92%
See 1 more Smart Citation
“…He et al. used titanic acid nanotubes as the precursor to prepare OV‐rich TiO 2 , with the help of the density functional theory (DFT) calculations combined with experimental characterization, they had clearly understand the synergy mechanism between vacancy and Pt atom in the photocatalytic reaction process [44] . From the electron spin resonance spectra (ESR) (Figure 5), the intensity of ESR signal about Pt‐VO‐TiO 2 ‐500 is stronger than VO‐TiO 2 ‐500, Indicating that the oxygen vacancy concentration of Pt‐VO‐TiO 2 ‐500 is higher than VO‐TiO 2 ‐500.…”
Section: The Synergistic Effect Of Heteroatom Doping and Vacancymentioning
confidence: 99%